The Effect Of Role Conflict And Job Authority On Employee Job Satisfaction At Pt Erajaya Group, Bengkulu City - Meilaty Finthariasari; Ririn Harini; Eti Arini; Nio Firdaus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the Conflict of Role and Work Authority on Job Satisfaction of employees at PT. Erajaya Group Bengkulu City, either partially or simultaneously. There are several factors that will be discussed in this study, including Role Conflict and Work Authority. The object of this research is the employees of PT. Erajaya Group Bengkulu City, totaling 37 people. In this study the authors used data collection methods by means of observation, distributing questionnaires or questionnaires and interviews. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear analysis, determinant coefficients, and also hypothesis testing. From the results of the tests that have been carried out, it can be concluded that the Role Conflict (X1) and Job Authority (X2) variables have a partial or simultaneous effect on employee job satisfaction at PT. Erajaya Group Bengkulu City. From the results of multiple linear regression, the regression equation obtained is as follows: Y = 1.420 + 0.536 (X1) + 0.626 (X2).